Recria de bezerras de corte em pastagem de azevém submetidas à suplementação autolimitante - Domingues, Camille Carijo (2022)
The rearing production system in beef cattle must be understood as a determining factor for the success of the livestock sector. This work aimed to study the strategy of self-limiting supplementation in ryegrass pasture, which can be adopted in order to enhance the rearing production of beef calves. The adoption of technological strategies aims to improve the production rates of a herd, making the activity viable, competitive and profitable. The most important factor associated with profitability within a rearing system is productive and reproductive performance, therefore, management strategies such as supplementation, nutritional requirements of females, adequacy of age at first mating, and seasonal variation in forage production, become fundamental tools to increase the productive efficiency and, consequently, the reproductive efficiency of a herd. It is extremely important to analyze the efficient use of the self-limiting supplement within a production system such as rearing, making it possible to plan and implement an action plan to intensify production, as it is based on autonomy in supplement intake, that is based on the use of feeders with a deposit where cattle consume available food for several days. Self-consumption supplementation may contain an amount of salt or other limiting factor to regulate the consumption of the supplement and avoid disturbances in the bovine rumen. This study presented relevant results in relation to productive and reproductive performance, heifers that consumed a self-limiting supplement obtained an average daily gain 25,0% higher compared to heifers exclusively on ryegrass, in addition to reducing the consumption of dry matter from the pasture by 18,1% compared to calves exclusively on ryegrass to heifers exclusively on pasture. Heifers receiving a self-limiting supplement showed an increase in the evolution of body weight, causing a reduction in days spent on pasture, as well as better gains in weight:height and body condition score, improving reproductive development in relation to heifers exclusively on ryegrass. With this, the self-limiting supplementation takes into account the manpower, costs and profitability of the applied technology.